La influencia de la ideología neoconservadora en la gestación y conducción de la guerra de Irak - Torres Soriano, Manuel R. (UNISCI Discussion Papers, 2007)
Understanding the logic of a war requires us to explore the ideology on which some of its fundamental decisions are based. This article starts from the assumption that the U.S. invasion of Iraq in 2003 was strongly influenced by some of the theoretical tenets of the neoconservative thinking. In this study, some of this conflict’s main episodes – threat perception, military planning, political previsions, etc. – are analyzed, interpreting them as an attempt of the decision makers to achieve coherence with the basic preconceptions and ideas of that ideology.